2021
DOI: 10.31557/apjcp.2021.22.7.1987
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk From Modifiable and Non-Modifiable Risk Factors among Palestinian Women: A Systematic Review and Meta-Analysis

Abstract: Objective: Breast cancer (BC) is known as one of the deadliest forms of cancer, and it is increasing globally. Identifying risk factors for BC is a key point in developing preventive strategies to reduce its occurrence. Herein, we aimed to conduct a systematic review and meta-analysis focus on the risk factors for BC in Palestine. Material and Methods: We performed a systematic search via PubMed, MEDLINE, SCOPUS, Science Direct, Cochrane library, Emerald Insight, and Google scholar for identifying studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the current study found secondhand smoke to be a major risk factor of BC in both female and male patients. Similarly, recent studies also found the relation between passive smoking and risk of BC, and this highlights the importance of protecting women at a higher risk of BC due to exposure to secondhand smoke ( 42 , 65 ).…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, the current study found secondhand smoke to be a major risk factor of BC in both female and male patients. Similarly, recent studies also found the relation between passive smoking and risk of BC, and this highlights the importance of protecting women at a higher risk of BC due to exposure to secondhand smoke ( 42 , 65 ).…”
Section: Discussionmentioning
confidence: 57%
“…According to the study's findings, BC is less likely to occur in females who have not yet reached menopause than it is in females who have (OR= 0.428, 95%CI, 0.258, 0.710). Similarly, Arafat et al, (2021) reported the same findings in a meta-analysis on BC risk from modifiable and non-modifiable risk factors in Palestinian women (Arafat et al, 2021). Additionally, Sangrajrang et al, (2013) found a statistically significant link between higher BC risk and postmenopausal women.…”
Section: )mentioning
confidence: 73%
“…Com relação à idade, sabe-se que esse é um dos principais fatores de risco relacionados ao câncer de mama, portanto, a probabilidade de desenvolver a neoplasia é diretamente proporcional a idade (16). Ao comparar o presente estudo com a literatura pode-se confirmar essa relação, visto que idade acima de 40 anos se mostra estatisticamente significativa como fator de risco não modificável para o câncer de mama (17,18).…”
Section: Discussionunclassified